Acetazolamide and human carbonic anhydrases: retrospect, review and discussion of an intimate relationship - Dimitrios Tsikas (Taylor & Francis Group, 2024)
AbstractAcetazolamide (AZM) is a strong pharmacological sulphonamide-type (R-SO2-NH2, pKa 7.2) inhibitor of the activity of several carbonic anhydrase (CA) isoforms, notably of renal CA II (Ki, 12 nM) and CA IV (Ki, 74 nM). AZM is clinically used for about eighty years in various diseases including epilepsy and glaucoma. Pharmacological AZM increases temporarily the urinary excretion of bicarbonate (HCO3-) and sodium ions (Na+) and sustainably the urinary pH. AZM is excreted almost unchanged over several hours at high rates in the urine. Closely parallel concentrations of circulating and excretory AZM are observed upon administration of therapeutical doses of AZM. In a proof-of-principle study, we investigated the effects of the ingestion of a 250-mg AZM-containing tablet by a healthy volunteer on the urinary excretion of organic and inorganic substances over 5 h (range, 0, 0.5, 1, 1.5, 2, 3, 4, 5 h). Measured analytes included: AZM, amino acids and their metabolites such as guanidinoacetate, i.e. the precursor of creatine, of asymmetrically (ADMA) and symmetrically (SDMA) dimethylated arginine, nitrite (O = N-O-, pKa 3.4) and nitrate (O2N-O-, pKa −1.37), the major metabolites of nitric oxide (NO), the C-H acidic malondialdehyde (MDA; (CHO)2CH2, pKa 4.5), and creatinine for correction of analytes excretion. All analytes were measured by validated isotopologues using gas chromatography-mass spectrometry (GC-MS) methods. AZM excretion in the urine reached its maximum value after 2 h and was fairly stable for the next 3 h. Time series analysis by the ARIMA method was performed. AZM ingestion increased temporarily the urinary excretion of the amino acids Leu + Ile, nitrite and nitrate, decreased temporarily the urinary excretion of other amino acids. AZM decreased sustainably the urinary excretion of MDA, a biomarker of oxidative stress (i.e. lipid peroxidation). Whether this decrease is due to inhibition of the excretion of MDA or attenuation of oxidative stress by AZM is unknown. The acute and chronic effects of AZM on the urinary excretion of electrolytes and physiological substances reported in the literature are discussed in depth in the light of its extraordinary pharmacokinetics and pharmacodynamics. Tolerance development/drug resistance to AZM in chronic use and potential mechanisms are also addressed.